R. Evans papers - Evans, R.
Correspondence, notes, and copies of writings pertaining to witchcraft, astrology, spiritualism, etc.
In part, handwritten transcripts.
Spiritualist.
Collection material in English.
Keywords: Astrology; Spiritualism; Witchcraft; Spiritualists